1972
DOI: 10.1126/science.176.4030.68
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and Environmental Interactions in the Behavioral Development of the Rat: Long-Term Effects

Abstract: The behavioral effects of early malnutrition and early environmental isolation were observed in male rats. Dietary and environmental manipulations occurred during the first 7 weeks of life, after which followed a 10-week recovery period. On the basis of several different responses, it was found that the behavioral effects of early malnutrition were exaggerated by the environmental isolation. In most cases, the behavioral effects of early malnutrition were completely eliminated by supplying "additional stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
87
3
14

Year Published

1978
1978
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(118 citation statements)
references
References 22 publications
13
87
3
14
Order By: Relevance
“…These results confirm previous reports of high activity levels following isolation rearing in the rat (e.g., Levitsky & Barnes, 1972;Sahakian et al, 1975) and provide important information regarding the stability of this difference and the possibility of obtaining a stable behavioral baseline for drug investigation. Although all groups decreased in activity over the first few days of testing, the heightened activity of isolation-reared animals is long-term and the difference between isolated and socially reared a.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These results confirm previous reports of high activity levels following isolation rearing in the rat (e.g., Levitsky & Barnes, 1972;Sahakian et al, 1975) and provide important information regarding the stability of this difference and the possibility of obtaining a stable behavioral baseline for drug investigation. Although all groups decreased in activity over the first few days of testing, the heightened activity of isolation-reared animals is long-term and the difference between isolated and socially reared a.…”
Section: Discussionsupporting
confidence: 80%
“…Since the young rat normally engages in a very high level of social activity, it is not surprising that social and/or environmental impoverishment can have pronounced effects upon adult behavior. For example, isolated animals differ from communally raised or socially enriched animals in that isolated animals are commonly found to be more active (e.g ., Levitsky & Barnes, 1972;Sahakian, Robbins, Morgan, & Iversen, 1975;Valzelli, 1969), have larger adrenal glands (Geller, Yuwiler, & Zolman, 1965;Hatch, Wiberg, Baloza, & Grice, 1963), and generally do not perform as well in learning tasks (Bingham & Griffiths, 1952;Morgan, 1973;Morgan, Einon, & Nicholas, 1975).…”
mentioning
confidence: 99%
“…Thus, reduced dopamine transporter and receptors in the striatum with early ID may reduce motivation, exploration and learning due to reduced input signaling positive internal reward. A related mechanism through which ID during infancy could have long-term effects is known as 'the functional isolation hypothesis' (Levitsky & Barnes, 1972;Lozoff et al, 1998;Strupp & Levitsky, 1995). According to this hypothesis, reduced activity and exploration and/or changes in affect and attention may lead ID infants to seek and receive less stimulation from the physical and social environment.…”
Section: Discussionmentioning
confidence: 99%
“…Frankova (1968) was the first to use two environmental conditions and showed that an interaction exists between early nutrition and early environment in open field behavior. Though some studies (Frankova, 1972;Levitsky & Barnes, 1972) reported a malnutritional effects on open field behavior in two or three levels of environment, such investigation are few, and the results were not consistent each other.…”
Section: Institute For Developmental Research Aichi Prefectural Cohanmentioning
confidence: 68%